An experimental study of hydroxylbastnasite solubility in aqueous solutions at 25 °C - Rodriguez-Blanco, Juan (My University, 2016)
The mobility of rare earth elements (REEs) in natural aqueous solutions is of increasing interest due to their application in numerous high-tech and renewable energy technologies (e.g., wind turbines and electric vehicles), as well as their role as tracers in the Earth Sciences. Basic thermodynamic data for water–rock interactions are, however, sparse and partially inconsistent, even for carbonate minerals of the bastnasite group (REE(CO3)(OH,F)), which currently represent the most exploited REE ore. Towards the improved quantification of the REE in natural and industrial systems, pure hexagonal hydroxylbastnasite and orthorhombic kozoite (REE(CO3)(OH)) were synthesized at hydrothermal conditions and subsequently used as starting material for aqueous dissolution and precipitation experiments. All closed system experiments were performed in air equilibrated aqueous fluids. Reaction progress was followed by measuring pH and REE concentrations at regular intervals. Experiments at 25 °C in the presence of selected concentrations of HCl and NaOH were run for up to 33 days until steady-state pH and REE concentrations were attained. Results indicate that the solubility products (KSP) of the reaction REE(CO3)(OH) = REE3 + + CO32− + OH− are log(KSP) = − 23.8 ± 0.1, − 24.1 ± 0.3, and − 22.3 ± 0.2 for Nd-, La-hydroxylbastnasite, and Nd-kozoite, respectively at 25 °C.
PUBLISHED
Keywords: Bastnasite; Kozoite; Solubility; Carbonate; Thermodynamics; Rare earth elements (REEs); Smart & Sustainable Planet